Pendidikan Khusus dan Anak Berbakat - zuimar ilyas (Universitas Islam Negeri Sumatera Utara Medan, 2019)
Basically gifted children have different characteristics with children in general. Advantages of these gifted children whom they thought was the power that exceeds any other normal children. These differences have implications for educational practices in schools. Teachers as teachers, educators, trainers and mentors for gifted children are expected to have sufficient knowledge at the level of theory and practice.